4*(50+x)+3800*(50+2x)=6.13

Simple and best practice solution for 4*(50+x)+3800*(50+2x)=6.13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4*(50+x)+3800*(50+2x)=6.13 equation:


Simplifying
4(50 + x) + 3800(50 + 2x) = 6.13
(50 * 4 + x * 4) + 3800(50 + 2x) = 6.13
(200 + 4x) + 3800(50 + 2x) = 6.13
200 + 4x + (50 * 3800 + 2x * 3800) = 6.13
200 + 4x + (190000 + 7600x) = 6.13

Reorder the terms:
200 + 190000 + 4x + 7600x = 6.13

Combine like terms: 200 + 190000 = 190200
190200 + 4x + 7600x = 6.13

Combine like terms: 4x + 7600x = 7604x
190200 + 7604x = 6.13

Solving
190200 + 7604x = 6.13

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-190200' to each side of the equation.
190200 + -190200 + 7604x = 6.13 + -190200

Combine like terms: 190200 + -190200 = 0
0 + 7604x = 6.13 + -190200
7604x = 6.13 + -190200

Combine like terms: 6.13 + -190200 = -190193.87
7604x = -190193.87

Divide each side by '7604'.
x = -25.01234482

Simplifying
x = -25.01234482

See similar equations:

| 7(-2x+4)+6=7x-21 | | 4*(50+x)+3800*(50+2x)=6.13whatisx | | 3n+m= | | 10x+6-(3x-3)-(3x-3)= | | X=X+273 | | 5-/y-13/ | | 21b-13=29 | | 21b-13=19 | | 5(2x+6)=4(-5-2x+3x) | | 10x+5=-15 | | 1+8x-8=-10 | | 1/2(n-4)=16 | | X=2(10-x) | | 10*x=6*(3+x) | | x-37/9=7 | | 5.8-2.9-7.8= | | 4*(50+x)+3800*(50+2x)= | | 2(X+1)+2(X+1)=24whatisX | | -5(m+8)=-2(m+8) | | -4=x-3/2 | | 3-2y-1=4y-7 | | 4x-18=9x+6 | | -9(4-x)-(1+7x)=-25 | | X+3y+27=0 | | 3/4×4= | | 9+2x+14=x+17 | | 3+c=13 | | 4/5÷8/9= | | 3a-4=-9 | | 4/5x-4=12 | | x^2y-3xy^2= | | -8y+24=-5(y-6) |

Equations solver categories